Bispecific Antibodies: From Research to Clinical Application - Ma, Jiabing; Mo, Yicheng; Tang, Menglin; Shen, Junjie; Qi, Yanan; Zhao, Wenxu; Huang, Yi; Xu, Yanmin; Qian, Cheng (Frontiers in Immunology, 2021)
Bispecific antibodies (BsAbs) are antibodies with two binding sites directed at two different antigens or two different epitopes on the same antigen. The clinical therapeutic effects of BsAbs are superior to those of monoclonal antibodies (MoAbs), with broad applications for tumor immunotherapy as well as for the treatment of other diseases. Recently, with progress in antibody or protein engineering and recombinant DNA technology, various platforms for generating different types of BsAbs based on novel strategies, for various uses, have been established. More than 30 mature commercial technology platforms have been used to create and develop BsAbs based on the heterologous recombination of heavy chains and matching of light chains. The detailed mechanisms of clinical/therapeutic action have been demonstrated with these different types of BsAbs. Three kinds of BsAbs have received market approval, and more than 110 types of BsAbs are at various stages of clinical trials. In this paper, we elaborate on the classic platforms, mechanisms, and applications of BsAbs. We hope that this review can stimulate new ideas for the development of BsAbs and improve current clinical strategies.